The Oppemei Model on Creative Thinking Skills Reviewing From Self-Efficacy of Students in Science Learning - I Gusti Ayu Tri Agustiana; I Nyoman Tika; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2023)
The The current problem is that it is still very difficult to develop creative thinking skills and self-efficacy in children. This is because there is still a high sense of wanting to win alone and limited learning time at school. The main aim of this research is to analyze the OPPEMEI model for creative thinking skills in terms of the self-efficacy of fourth grade elementary school students in learning science. The population of this research is all 186 grade IV students. This type of research is a quasi-experiment with a non-randomized design.PosttestOnly Control GroupDesignand 2x2 factorial as the analysis design. The classes used as samples were determined using random sampling techniques. Data collection methods use questionnaires and tests. The instrument uses questionnaires and question sheets. Data analysis techniques are descriptive qualitative and descriptive quantitative using two-way analysis of variance (ANOVA). The research results show that there are differences in creative thinking skills between students who follow the OPPEMEI learning model and students who follow the conventional learning model. There are differences in creative thinking skills, in groups of students who have high self-efficacy who follow the OPPEMEI learning model and students who follow conventional learning models. There are differences in creative thinking skills, in the group of students who have low self-efficacy who follow the OPPEMEI learning model and students who follow the conventional learning model. It was concluded that there was an interaction effect between the learning model and self-efficacy on students' creative thinking skills in science subjects.